Respuesta :

Answer:

- [tex]\sqrt{3}[/tex]

Step-by-step explanation:

Using the trigonometric identity

cot x = [tex]\frac{1}{tanx}[/tex]

Thus

tan( [tex]\frac{11\pi }{6}[/tex]) = - tan ([tex]\frac{\pi }{6}[/tex])

Since [tex]\frac{11\pi }{6}[/tex] is in the fourth quadrant where tan < 0

and

2π - [tex]\frac{11\pi }{6}[/tex] = [tex]\frac{\pi }{6}[/tex] ← related acute angle

Then

- tan([tex]\frac{\pi }{6}[/tex]) = - [tex]\frac{1}{\sqrt{3} }[/tex], hence

cot ([tex]\frac{11\pi }{6}[/tex]) = [tex]\frac{1}{\frac{1}{-\sqrt{3} } }[/tex] = - [tex]\sqrt{3}[/tex]

ACCESS MORE